Regulatory governance in the Latin American telecommunications sector (2003)
Starting with Chile in the early 1980s, Latin American countries have pushed telecommunications reform to create regulatory environments that encourage private investment, especially foreign investment. I look at trends in 25 Latin American and Caribbean countries during 1980-2001 and construct an index based on the following aspects: autonomy, accountability, clarity of roles and objectives, transparency and participation, and the type of legal mandate that creates a regulatory body. The index shows clearly that, in general, most countries embraced strong regulatory reforms along the lines recommended by experts and practitioners. The index also correlates well with main political, risk, economic and telecommunications variables. © 2003 Elsevier Ltd. All rights reserved.